Violence Against Women: Contributions from Latin America - Sagot Rodríguez, Montserrat (2020)
Beginning in the 1980s, Latin American feminist movements identified violence against women as one the main social problems in the region, resulting from a system of gender oppression intertwined with economic and political oppression. This chapter discusses Latin American scholarship’s most important theoretical contributions to the study of violence against women, as well as the proposals for addressing the problem and the controversies around those proposals. The chapter first traces the analyses of this form of violence under dictatorships. It then addresses how the transition to democracy afforded feminists opportunities to put the issue on the public agenda. The chapter also presents new concepts that have been developed to understand the escalation of lethal violence, as well as Latin American scholars’ and activists’ most recent strategies for ending violence against women.